Media use, anti-Americanism and international support for the Iraq War - Willnat, Lars; Aw, Annette; Hamdy, Naila Nabil; He, Zhou; Menayang, Victor; La Porte, María Teresa; Sanders, Karen; Tamam, Ezhar (Sage, 2006)
This study investigates the impact of pre-war news coverage on international support for President Bush's decision to invade Iraq in 2003. The study is based on a survey conducted one week prior to the start of the Iraq War among 1787 university students from six countries in Europe, Asia and the Middle East. The findings indicate that exposure to pre-war news coverage was associated with more positive attitudes toward Iraq and higher levels of fear related to the possible consequences of a war. Stronger international support for a US invasion correlated with more positive attitudes toward Iraq, less fear about a possible war and lower levels of anti-Americanism. Copyright © 2006 Sage Publications.